Respon Masyarakat Desa Cibalung Terhadap Teknologi Berbasis Web Guna Membantu Pemasaran Produk Olahan - Adam Anom Jati; Lisma Aulia Rohmah; Lidya Hawila Sallo; Mahda Aryo Firdaus; Destriana Nur; Muhammad Fauzan Lazwar; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This research aims to help MSMEs in Cibalung Village through the creation of a website with features that are specially designed according to the wishes and needs of the MSMEs in the village. The creation of this website involves several respondents in Cibalung Village which includes Farmers, MSME business actors, Housewives, and freelancers. The website that was created is intended as an information media about agricultural cultivation, fisheries and livestock and marketing that can be used to introduce and promote processed products for the community in the village. Data collection was carried out with a survey using a questionnaire with 21 questions and reinforced by interviews. based on the results of interviews and questionnaires obtained with 30 respondents from the entire UMKM population in Cibalung Village.